Interdigitized capacitive humidity sensor using FR4 printed circuit board material without sensitive layer - Setyawan Purnomo Sakti; Jessica Alfa Aini; Shania Rachmi; Elsa Hedya Kusumaningtyas; Irma Azizah; Triswantoro Putro; Dewi Anggraeni (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2026)
Humidity sensors are widely used across numerous applications, including agriculture, health, industry, environmental monitoring, and high-risk environments such as chip fabrication rooms. Interdigital capacitors (IDCs) are among several humidity-sensing designs that have been developed, and they are attractive due to simple fabrication and easy integration with electronic systems. We developed an IDC humidity sensor on a glass-epoxy substrate (FR4) using a standard commercial printed circuit board (PCB) production process. Without additional sensitive layer, the sensor production is simple. The sensor design was explored by varying electrode width. Calibration was performed in a self-constructed chamber over a relative humidity range from 15% to 90%. The IDC sensor was benchmarked against a standard humidity measurement instrument. The IDC capacitance showed a linear correlation with relative humidity, with a correlation coefficient of at least 0.98. With the finest track and spacing size of 0.254 mm achievable via commercial PCB manufacturing and a sensor footprint of 10×10 mm, the capacitance falls in the pF range, compatible with most available electronic devices. The sensitivity of the developed sensors is 2.361×10-4, 2.361×10-4, 2.361×10-4 picofarads for a track width of 0.254 mm, 0.3048 mm and 0.3556 mm respectively. These results indicate that mass production of IDC humidity sensors could be achieved at a low cost. The combination of small feature sizes and a compact sensor footprint support practical integration into existing electronic systems.